Enhancing the Effectiveness of Public Spending in Switzerland - Joumard, Isabelle (OECD Publishing, 2002)
Switzerland is a highly decentralised country with large spending and revenue-raising powers devolved to cantons and municipalities. The federal system, in combination with an extensive use of direct democracy, has contributed to keep public spending at a relatively low level in international comparison. It has also made it possible to tailor the provision of public services to citizens' needs and willingness to pay and to experiment with a variety of policies. At the same time, several tensions have emerged and effective control of spending deteriorated during the 1990s. After identifying these tensions, this paper reviews recent policy initiatives and proposes options for further enhancing public spending effectiveness. These entail implementing a new fiscal rule which will allow the free play of the automatic stabilisers at the federal level and ensuring its consistency with other government levels' behaviour; increasing transparency in public spending costs and ...
Keywords: Economics; Switzerland